Television in infancy and early childhood--Uses & effects - Murray, John P.; Murray, Ann D. (Elsevier/Academic Press, 2008)
The use of television and other media—such as video, computer programs, and CD material—in infancy and early childhood can have both positive and negative influences on the intellectual and social development of young viewers. Viewing carefully designed programs for preschool age children, such as Sesame Street and Mister Rogers’ Neighborhood, can have positive effects on social skills and academic preparation that enhance children’s development in preschool, early school years and even into adolescence. At the same time, early use of screen media in infancy and toddlerhood, without the intensive support of parents and other caregivers, can disrupt the development of social skills that are normally acquired through consistent and continuous interaction with parents and significant others in the infant’s environment. The history of 50 years of research on children and television has demonstrated consistent and persistent media effects across a wide range of experimental and correlational studies. Recent advances in neurological research, including brainmapping and the discovery of mirror neurons, leads to expanded concerns.
Keywords: Television; Infants; Children; Neurology; Cognitive development; Social behavior